Manajemen kualitas platform metabase GIS data analysis berbasis cloud berdasarkan indikator ISO 9126 - Purbaningtyas, Rani; Widianta, Moh Munih Dian; Albaab, Mochammad Rifki Ulil (JURNAL INFOTEL, 2024)
Platform metabase GIS data analysis based on the cloud that has been successfully developed is an alternative solution for spatial-text data analysis. The output of this cloud-based platform not only provides accurate textual information but also precise location representation of the objects. This research examines the quality of the developed platform based on ISO 9126, which consists of six main indicators: functionality, reliability, feasibility, efficiency, maintainability, and portability. Each indicator has different sub-indicators, totaling 22 sub-indicators. The quality assessment results indicate that the platform for metabase GIS data analysis based on the cloud exhibits excellent quality, with an average test result based on the ISO 9126 indicators reaching 93%.